2006
DOI: 10.1080/0028825x.2006.9513030
|View full text |Cite
|
Sign up to set email alerts
|

A morphological comparison of leaf heteroblasty between New Caledonia and New Zealand

Abstract: Leaf heteroblasty, or pronounced changes in leaf morphology during plant development, is a conspicuous phenomenon on many isolated islands. However, morphological comparisons have not been made between islands, and the processes responsible for island heteroblasty are poorly understood. We investigated differences in leaf morphology of heteroblastic trees and shrubs in New Caledonia and New Zealand. Heteroblastic leaves were collected in field searches in several comparable habitat types in both countries. Lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Alternatively, it could be associated with herbivory (Rausher 1978). Heteroblasty (i.e., sudden, significant changes in morphology during ontogeny) is a common feature in the New Zealand flora (see Cockayne 1912;Day 1998;Burns and Dawson 2006). Heteroblasty is often attributed to extinct browsing birds (see Givnish et al 1994;Bond et al 2004;Bond and Silander 2007).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Alternatively, it could be associated with herbivory (Rausher 1978). Heteroblasty (i.e., sudden, significant changes in morphology during ontogeny) is a common feature in the New Zealand flora (see Cockayne 1912;Day 1998;Burns and Dawson 2006). Heteroblasty is often attributed to extinct browsing birds (see Givnish et al 1994;Bond et al 2004;Bond and Silander 2007).…”
Section: Resultsmentioning
confidence: 98%
“…Extant ratites swallow leaves by positioning them in their bill and then snapping their head forwards to orient leaves down their oesophagus, in a manner similar to herons when swallowing fish (Bond et al 2004). Long, narrow leaves could therefore be more difficult for toothless birds to swallow, and are produced by juvenile plants of many heteroblastic species (Burns and Dawson 2006), including two of the three largest tree species studied here (Eleaocarpus dentatus and Knightia exsesa).…”
Section: Resultsmentioning
confidence: 99%
“…Future work would also benefit from considering other archipelagos and perhaps changes in plant traits through ontogeny (e.g. Burns & Dawson, 2006, 2009; Fadzly et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In order to deter bird browsers, plants need other types of defense. [15][16][17][18][19][20] Fadzly et al 12 found that color may have been a critical component of a defensive strategy that evolved in P. crassifolius to deter moa browsing. Spectrographic analyses of seedling leaves from the perspective of birds indicate that their mottled brown color would have made them very difficult for moa to locate amongst a background of leaf litter on the forest floor.…”
Section: Is Crypsis a Common Defensive Strategy In Plants?mentioning
confidence: 99%